(untitled) (Journal of Science and Technology, 2016)
To provide guidelines fiat consumers and dietitians, (Nang.; Protein Maize (QP.5I) meal and Anchovies fish were analyzed for nutrient and energy content. separately, and in varying supplementation mixtures. QPM meal (Banku) was prepared by traditional procedure, subsequently twos dried and milled to facilitate determination of proximate composition. using Association of Analytical Chemists (A.O.A.C) methods per 100g of dry matter. Carbohydrate content was determined by difference. Similar analysis was performed on Anchovies fish alone. and as 5%, 1516, 2111%. and 25% supplements of the QPM Banku Anchovies fish had the same content of moisture, threefold protein, fourfold fat, one-third crude fiber, fourfold ash. and one-eighth the energy content of on supplemented (1,31 Mamba. Supplementation o/ (1113l Bunko with 5% Anchovies fish increase) protein content per 2Og from 2110g to 2g. for front 1.0g to 1..1g, ash from 2.g to 3.0g. energy from 325.0A cal to 329.5104 and domed crude fiber from Liz to tag, and carbohydrate front 39.6g 10 57,11g. Nutrient content of QP31 Bantu did not vary for 5% and 10% anchovies supplementation, bat there was a decrease in energy to 324.1kcat There was also a gradual increase in nutrients from 15% to 25% supplementation. Energy content. however, decreased from 327.5kcal to 111.4kcal. and carbohydrate from 47.11e to 47.6e per hug with increase in level of supplementation from 5% to 25,6 On the basis the daily dietary protein and energy requirements for pre-school children, 5% supplementation of QPM Banku with Anchovies fish was found to be adequate.